تأثير خلائط تربة التغطية في إنتاجية الفطر الزراعي (Agaricus bisporus) - زيدان, رياض; يبرق, محمد موفق; الياس, إنعام (Latakia University Journal -Biological Sciences Series, 2013)
تمت دراسة تأثير خلط بعض المواد المتوفرة محلياً ورخيصة الثمن (رمل نهري, برلايت, نشارة الخشب, نحاتة) مع البيتموس في تحضير تربة التغطية لمزارع إنتاج الفطر الزراعي. و تضمن البحث 14 معاملة. أظهرت النتائج أن إضافة نشارة الخشب والبرلايت إلى البيتموس بنسبة 10, 20, 30%أسهمت في زيادة قدرة تربة التغطية على الاحتفاظ بالماء قياساً بباقي المعاملات فكان له دور ايجابي في زيادة انتاج الفطر الزراعي بشكل معنوي في الأسبوع الأول وسجلت معاملة إضافة نشارة الخشب 20% أعلى انتاج في نفس الأسبوع، إذ بلغ 16.33 كغ/م2 قياساً بالشاهد 9.5 كغ/م2 ، إضافة إلى زيادة كمية إنتاج الأسبوعين الأول والثاني (26 كغ/م2) مقابل ( 21.5كغ/م2) للشاهد. أدت جميع معاملات إضافة نشارة الخشب إلى زيادة كمية الإنتاج الكلي بفروق معنوية قياساً بالشاهد, بينما تفوقت معاملة الشاهد معنوياً على باقي المعاملات وقد أعطت معاملة إضافة النحاتة بنسبة 30% أدنى انتاج كلي 8.17 كغ/م2 , وأدت إضافة البرليت بنسبة 20% ونشارة الخشب بنسبة 10, 20 , 30% إلى زيادة الربح الصافي ومعامل الربحية قياساً بالتكاليف. This research studies the effect of mixing some locally available and cheap materials such as river sand, berlite, saw dust and lime powder with peat-moss as an alternative to pure peat-moss in making the casing layer of mushroom basins. Research includes 14 treatments. The results show that saw dust and berlite at levels of 10, 20 and 30% with peat-moss contribute in increasing the capacity of the water retention of the casing soil, compared with other treatments, having thus a positive role in increasing the production of the agricultural mushroom significantly in the first week. Saw dust treatment at 20% level recorded (16.33 kg/m2) in the same week, which is the highest production rate in comparison with the control treatment (9.5 kg/m2). Also, the total production of the first and second weeks recorded (26 kg/m2) for the 20% saw dust treatment compared to (21.5 kg/m2) for the control. A significant increase has been recorded in the amount of total production in all saw dust treatments, and decline in the rest of the treatments in comparison with the control. The lowest production of mushroom was (8.17 kg/m2) with lime powder treatment at 30% level. The treatments of saw dust levels of 10, 20 and 30% and berlite 20% registered an increase in the net profit and the earning potentials compared to the cost of production.